Madheshi Women’s Struggles against Discrimination in Nepal (KMC Journal, 2024)
Madheshi women experience various ways of discrimination in Nepali society. They suffer from race, caste, class and gender-based discrimination in society. In this context, this study explores the experiences and perceptions of Madheshi women about discrimination based on race, gender, class, caste/ethnicity, age and education through qualitative research. Eighteen participants were selected through purposive sampling. An in-depth interview was conducted with fourteen Madheshi women from various backgrounds and four Madheshi males were the key information participants. The Madheshi women from various backgrounds experienced discrimination and marginalization based on caste/ethnicity, class, race, gender, age and education. Madheshi women are not a homogeneous group, as they experience different kinds of exclusion in diverse settings. This study suggests enhancing the respect and recognition of Madheshi women in society. Furthermore, it suggests implementing and formulating relevant policies and legislation for Madheshi women, considering the prevalence of discrimination faced by Madheshi women in Nepal.